Graduate Level Training in Nutrition: An Integrated Model for Capacity Building- A National Report - Robabeh Sheikholeslam; Hossein Ghassemi; Osman Galal; Abolghassem Djazayery; Nasrin Omidvar; Issa Nourmohammadi; Ma Antonia G Tuazon (Tehran University of Medical Sciences, 2015)
Iran has been active in human nutrition training for the past five decades, but the existing curricular programs do not equip the graduates with the knowledge and skills required for solving food security and nutritional problems of the country. Given this, the Nutrition Department (ND) of Iran's Ministry of Health and Medical Education (MOHME) initiated a curricular reform to develop responsive graduate programs in key areas of nutrition that fill the existing gaps in nutrition training with the goal of improving nutrition policy-making and program development, implementation and evaluation. ND called for a request for proposals for a project entitled "Graduate Level Training in Nutrition". Specifically, with technical assistance from leading academic institutions in Asia, North America and UK, seven new graduate programs were housed in three separate institutions, but coordinated so that together they form a broad multidisciplinary resource for graduate education and research. These seven-degree programs are MSc and PhD in Molecular/Cellular Nutrition, MSc and PhD in Nutritional Epidemiology, MSc and PhD in Food Policy and Nutrition Intervention, and MSc in Community Nutrition. The programs were prepared in collaboration and active participation of selected faculty members of the three Iranian universities, International Union of Nutritional Sciences and the University of Philippines at Los Baños. The development of these programs was made possible through a loan from the World Bank, under the Second Primary Health and Nutrition Project in the MOHME.